Autosomal recessive hyper‐IgE syndrome successfully treated with hematopoietic stem cell transplantation. Issue 5 (24th July 2019) - Lopes, Jorge; Teixeira, Diogo; Sousa, Cristina; Baptista, Armando; Moreira, Diana; Ferreira, Eduarda O.
Abstract: Autosomal recessive hyper‐IgE syndrome is a primary immunodeficiency that results from a mutation in the DOCK8 gene. We report a case of a patient presenting with severe eczema, atopy, and recurrent skin infections since the first months of life. The diagnosis of autosomal recessive hyper‐IgE syndrome was made at the age of 7 by a positive DOCK8 genetic test. The patient underwent hematopoietic stem cell transplantation, with complete remission of the various manifestations.